Verses of Tolerance in the Qur'an: An Analysis from the Perspective of Tafsir Al-Azhar and Tafsir al-Qur'anul Majid - Abdullah, M. Yusuf; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Tolerance is an issue that holds its sensitivity and complexity. A misunderstanding or lack of awareness of the urgency of tolerance can be a detrimental trigger for conflict. Therefore, in the context of the existence of Muslims as the majority in this country, it is very important to explore the meaning of tolerance from the perspective of scholars. This research is based on Tafsir Al-Azhar and Tafsir Al-Quranul Majid, two works of Qur'an interpretation that greatly influence. Using a qualitative approach and literature method, this study aims to provide in-depth insight into the views of scholars regarding tolerance. The analysis results of the two interpretations indicate a common view in interpreting verses that contain a message of tolerance. Both interpretations agree that in the holy book of the Qur'an, there is a teaching that difference is a reality that is part of the will of Allah SWT. Furthermore, there is a message to uphold the teachings of Islam and invite people to Islam while still believing that there is no coercion in embracing religion. In other words, both recognize that the values of tolerance, as explained in the Qur'an, are the main foothold for realizing peaceful coexistence in a heterogeneous society. This study observes that a deep understanding of religious teachings can be a bridge to prevent the emergence of intolerance. Thus, further investigation into the context of tolerance from the scientific perspective of Islam contributes positively to strengthening the foundations of harmony and tolerance in the social life of mankind.